Designing and implementing development policy : the shift to holistics approaches and social policy frameworks - Thomas, Clive Y. (2002)
Examines the rationale behind the Social Policy Framework (SPF) approach. Characterises the region's social welfare regimes and elaborates the SPF proposal for the region.